Correlating volcanic dynamics and the construction of a submarine volcanogenic apron: An example from the Badenian (Middle Miocene) of North-Eastern Hungary. (April 2021) - Di Capua, A.; Barilaro, F.; Szepesi, J.; Lukács, R.; Gál, P.; Norini, G.; Sulpizio, R.; Soós, I.; Harangi, S.; Groppelli, G.
Abstract: This work studies a submarine volcanogenic apron forming the Nagyhársas Andesite Formation (Badenian – Middle Miocene) in the Mátra Mountains (North-Eastern Hungary), with the aim to identify volcanic processes, from the sedimentary bed scale to the architecture of the whole apron. Fieldwork has been carried out in two different localities (Tar and Sámsonháza villages), where eighteen logs have been measured and correlated, reconstructing the stratigraphic variations of the sedimentary beds and the volcano-sedimentary architectures of the proximal and distal part of the volcanogenic apron. Fifty-two samples have been collected, cut into standard thin sections and petrographically studied to support the interpretation of mechanisms that accumulated the volcanogenic detritus in the submarine realm, as well as to identify the possible volcanic source and how it interacted with the marine environment. The results allow for the first time to underline the importance of a correct interpretation of volcanongenic deposits in the constrain of regional sea level variations, and to discuss the role of active volcanic edifices in shaping the proximal and distal sedimentary architecture of volcanogenic aprons. In proximal areas, the correlation between eruptive cycles and excavation-infill cycles of apron channels suggests that major eruptive events are responsible for channel excavation, whereas minor eruptive events contributed to the infilling of those architectures. In distal areas, the large supply of volcanogenic sediments cannibalizes the sedimentary system, temporally inhibiting the progradation of carbonate platforms nearby the apron offshoots, as well as allows the bypass of topographic barrier (e.g., ridges) favouring mechanisms of sediment spill-over in areas where otherwise sedimentation would be prevented. Highlights: The volcanogenic apron of the Nagyharsas Andesite Formation has been studied. Fieldwork and thin section analyses allow the reconstruction of the sedimentary architectures. Volcanic cyclicity and evolution of the apron are correlated for the first time. Volcanogenic sedimentation rate interacts with carbonate platforms and accommodation space. Constrains on regressive – transgressive and transgressive – regressive sequences have been identified.